Colourful and antioxidant silk with chlorogenic acid: Process development and optimization by central composite design - Shahid, M. (Elsevier Ltd, 2017)
Both the conventional one-factor-at-a-time (OFT) optimization, in which one of the factors is varied maintaining the other parameters fixed at constant levels, and the central composite design (CCD) optimization, in which all factors are varied simultaneously, were carried out for silk dyeing with chlorogenic acid. The CCD experiments were designed with the help of Design-Expert 10.0.3 software (trial version) and used for evaluating the interactive effects of the four most important operating variables namely pH, temperature, time and dye concentration. The colour characteristics, fastness properties, FT-IR spectra and antioxidant activity of dyed fabrics were also evaluated. The silk fabrics dyed with chlorogenic acid displayed light yellowish brown colour, and exhibited good fastness properties and excellent antioxidant activity.